2020
DOI: 10.36688/imej.3.91-100
|View full text |Cite
|
Sign up to set email alerts
|

Review of tidal turbine wake modelling methods

Abstract: Enabling Future Arrays in Tidal (EnFAIT) is an EU Horizon 2020 flagship tidal energy project. It aims to demonstrate the development, operation and decommissioning of the world’s largest tidal array (six turbines), over a five-year period, to prove a cost reduction pathway for tidal energy and confirm that it can be cost competitive with other forms of renewable energy. To determine the optimal site layout and spacing between turbines within a tidal array, it is essential to accurately characterise tidal turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The quantity of surrounding ambient flow field will affect the rate of wake recovery. According to Jump et al, [9] and Gómez-Elvira et al, [22], wake recovery is the re-energisation process where the flow field recovers the lost velocity by transfer of momentum. Welty et al, [23] stated that the momentum would transfer from the faster moving layer to the slower moving layer.…”
Section: Results Of Parametric Studymentioning
confidence: 99%
See 3 more Smart Citations
“…The quantity of surrounding ambient flow field will affect the rate of wake recovery. According to Jump et al, [9] and Gómez-Elvira et al, [22], wake recovery is the re-energisation process where the flow field recovers the lost velocity by transfer of momentum. Welty et al, [23] stated that the momentum would transfer from the faster moving layer to the slower moving layer.…”
Section: Results Of Parametric Studymentioning
confidence: 99%
“…Researchers [9,10] defined that wake of turbine is the rotationality of flow within the region downstream of the turbine which experiences disturbed flow that is characterized by the reduced flow speed, the pressure differential, expanding area, increase of turbulence and swirl. One of the terms commonly used to describe behaviors of wake is the wake recover.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the identification of the physical features of the wake flow in horizontal axis turbines are consolidated after a great number of previously published studies, concerning the fluid flow through based on wind turbines or large hydrokinetic turbines with small solidity (e.g. [14][15][16][17][18][19]), where the blockage effect is smaller, due to the geometry of the rotor with three sparse blades and often with a low rotation speed. However, there is a lack of research on high-solidity turbines, which are typically found in small hydrokinetic turbines.…”
Section: Introductionmentioning
confidence: 99%